Digital Risks in Emerging Economies: Cyber Threat Escalation in Indonesia (2020–2023) - Rinaldo; Puspitasari, Devi (Data : Journal of Information Systems and Management, 2024)
Indonesia's rapid digital transformation over the past decade has brought with it a surge in cyber threats, posing significant risks to national security, economic resilience, and public trust. This study investigates the escalation of cyber incidents between 2020 and 2023, analyzing their trends, regulatory responses, and systemic vulnerabilities. Utilizing secondary data from national agencies and international platforms, the research employs both quantitative and qualitative methods to assess incident volumes and policy effectiveness. The results reveal a sharp rise in cyber incidents, from 88 million in 2020 to over 1.65 billion in 2021, driven largely by phishing, ransomware, and malware campaigns. Although regulatory frameworks such as BSSN Regulation No. 8/2020 and Presidential Regulations 82/2022 and 47/2023 represent important steps, enforcement remains weak, and sectoral coordination is limited. Investment in cybersecurity is critically low, averaging only 0.02% of GDP, while SMEs remain particularly vulnerable due to limited resources and awareness. Discussion of these findings highlights systemic barriers such as institutional fragmentation, insufficient technical capacity, and underdeveloped cybersecurity culture. The study emphasizes the importance of inter-agency collaboration, adaptive regulatory frameworks, and increased investment to build national resilience. Comparative insights from global best practices suggest that integrating stakeholder feedback and promoting continuous learning can significantly enhance threat response and governance outcomes. In conclusion, Indonesia's cybersecurity landscape requires urgent strategic realignment. A well-funded, coordinated, and flexible national cybersecurity framework is essential to protect the nation's digital infrastructure and foster sustainable digital development